The CD200 and CD200 receptor cell surface proteins interact through their N-terminal immunoglobulin-like domains. - Hatherley, D; Barclay, N (2004)
CD200 (OX2) is a broadly distributed cell surface glycoprotein that interacts with a receptor on myeloid cells (CD200R) involved in regulation of macrophage function. Both CD200 and CD200R contain two Ig superfamily domains like many other leukocyte membrane proteins. Site-directed mutagenesis of CD200R showed that, like CD200, it interacted through its N-terminal domain. This indicated that the cell-cell interaction spans four Ig superfamily domains and this distance is similar to many interactions found between T cells and antigen-presenting cells. This suggests that this topology is also important in interactions of CD200 on a variety of cells with CD200R on myeloid cells, and comparable contact sites may be important mediating regulation in other cell-cell interactions. The mutagenesis showed that the binding involved the predicted GFCC' face of its N-terminal domain, like that of CD200, suggesting that the interaction evolved from a homotypic interaction.